RETOLD: A European Project Digitises Memories of Experimental Archaeology for Their Preservation - Paloma González Marcén; Clara Masriera Esquerra (EXARC Journal)
The origins of the European RETOLD project, led by the international association EXARC, lie in a concern to preserve the heritage generated by archaeological open-air museums through the creation of a standardised system for collecting, digitising and disseminating knowledge (memories) of the processes of building reconstruction and handcrafted objects. The project has a duration of four years (January 2021 to December 2024) and will be realised through the creation of a platform where these memories can be stored in digital format, available both for technical staff and for the non-specialist public through, for example, the creation of narratives (storytelling) derived from the memories.